Electronic commerce – Australian business research challenges - Cronje, Tom; Xia, Junwen (Communication Economics and Electronic Markets Research Centre, 2011)
At present Australia experience good growth and prosperity in the mining sector whilst flattening and struggling situations occur in other sectors. E-commerce is regarded as an answer to improve the performance of many businesses, but it depends on many factors like specific sectors or industries in which businesses are operating, size of the business, e-commerce adoption by competitors, characteristics of the customer market, and own procurement efficiency. This paper explores available information about Australian businesses - how e-commerce is defined and the components that it consists of; publicly available media release information about e-commerce; and research statistics about it. The findings assist in identifying areas of information that future research should focus on to enable businesses to make proficient e-commerce strategic decisions.